Analysis of Flavonoid Compounds in the Fruit of Prunus Microcarpa - Jissain, Faiq H. S.; Majid, Sirwa N. (Sulaimani Journal for Pure and Applied Sciences, 2004)
The isolation and identification of flayonoid compounds, rutin and quercefin, in the fiuit of prunus microcarpa (Rosaceae) are described. The flavonoid compounds have been extracted and separated by paper chromatography, thin - lays.r - chromatography, and flash coloum chromatography, Two compounds, rutin and quercetin, rvere identified by IH-NMR, IR, and UV. Rutin was hydrolyzed by 2M HCI /30 min., followed by extracting with ethyl acetate. Quercetin rvas obtained fiorn the organic layer, and the aqueous layer was examined by paper chromatography and showed the presence of glucose and rhamnose. The compound rutin (glycoside flavonoid) was quantified and the concenfration found to be 57.081%.
Keywords: HNMR,flavonoids; prunus microcarpa; T L C